The Effect of Group Work on Students’ Speaking Skills - Hidayat, Andika Firdaus; Marhum, Mochtar; Nadrun, Nadrun; Kamaruddin, Abdul (Journal of English Language and Education, 2026)
Many seventh-grade students struggle with speaking skills due to limited linguistic knowledge and speaking anxiety, despite the expectations of the Merdeka Curriculum for junior high school learners to communicate effectively in English. To address these challenges, group work is often recommended as a strategy to reduce anxiety and increase student participation. However, most previous studies were conducted at higher education levels, leaving limited evidence for younger learners. Therefore, this study aims to investigate whether group work significantly improves the speaking skills of seventh-grade students at SMP Negeri 18 Palu. A quasi-experimental design was used, involving two intact classes of 28 students each. Both groups completed a pre-test and post-test consisting of three oral questions assessing fluency and comprehensibility. The treatment will be administered over six sessions, from the second to the seventh meeting. The experimental group will use the group work technique, while the control group will receive conventional instruction. The data were analyzed using the Mann–Whitney U Test because the scores were not normally distributed. The findings showed that although both groups demonstrated increased mean scores from pre-test to post-test, the significance value (p = 0.113) exceeded the 0.05 threshold. Thus, the null hypothesis (H0) was accepted, indicating that group work did not produce a statistically significant improvement in students’ speaking skills. These results suggest that group work may require longer implementation or additional support to yield stronger effects for junior high school learners.